(3GdeMGSHI GdeGdjI GdNGUI (B/s - (3MdhI MfGf, QVhGfs; (3LhRja, cMGdI LHQGFjd s ((3YeGf(B: s (3GdOGQ GdYdejI GdOhdjI h OGQ GdKbGaI ddfTQ h GdJhRjY(B, s, 2001)
(3jJfGhd gPG GdcJGH eMGSHI GdefTBJ PGJ GdGbSGe (B- (3JUeje GdSLdGJ GdeMGSHjI (B- (3WQb GdeMGSHI GdjOhjI (B- (3eMGSHI GdefTBJ PGJ GdaQhY GdOGNdjI GdeSJbdI (B- (3eMGTHI GdefTBJ PGJ GdaQhY GdOGNdjI GdJGHYI (B-(3GdeMGSHI GdOhdjI hGdaQhY GdNGQLjI (B- - (3HVGYI GdGeGfI (B- (3HjY Gdhcjd HVGYI GdGeGfI HGdGLd (B- (3GdHjY HGdJaSjWs
(3SdSdg GdcJH GdeMGSHjg (B3s
Keywords: (3GdeMGSHIs; (3GdeMGSHI GdOhdjIs; (3eMGSHI GdefTCJs